DEVELOPMENT OF A MODEL FOR ESTIMATED TO ESTRO OF DAIRY CATTLE USING FUZZY LOGIC - SANTOS, RODRIGO COUTO; NÄÄS, IRENILZA DE ALENCAR; LABIGALINI, MARCELO RICARDO (Revista Brasileira de Engenharia de Biossistemas, 2007)
The environmental animal it is a tool that comes from meeting the needs on producers by gatheringthe required knowledge about animal production and environmental assessment, mainly throughindexes of comfort. It is also through this science that is now possible to propose options forobservation around management of the production based on interaction animal/environment throughtheir evidence physiological and behaviors. A shortage in the sector of dairy livestock Brazilian,both to increase the productivity as to reduce production costs, has led producers to seek newknowledge. Thus, the relationship between environmental factors and physiological responses ofdairy cattle are very important during the production process. Thus, information such as the timeof occurrence of estrus right should not be analyzed as a variable absolute, since environmentalfactors, system of creation and types of facilities in influencing physiological reactions of animal.This research had the objective to describe a model with multiple use of fuzzy logic for predictingthe estrus of dairy cows. There was used relevant information related to Holstein dairy cattlehoused in total confinement with distinct ranges of age, weight and production pre-defined. Servedas input variables of the Index of Temperature and Humidity (ITU), after last period rutting (PAUC)and number of signs of estrus (NCO). As output variable was the rate of estrus detection (TDC).It was possible to conclude that in conditions of high Index of Temperature and Humidity (ITU) themodel based on fuzzy logic estimated with a high degree of accuracy the possibility of a cowpresent estrus.